Epizootic Situation on Anaplasmosis of Small Ruminants in the Irkutsk Region - O. V. Suntsova; V. A. Rar; O. V. Lisak; I. V. Meltsov; E. K. Doroschenko; Yu. S. Savinova; A. Yu. Tikunov; I. V. Kozlova (Acta Biomedica Scientifica)
Anaplasmosis of ruminants is a group of natural focal infections caused by bacteria from the genus Anaplasma of the Anaplasmataceae family. The main etiological agent of anaplasmosis in sheep, goats, and wild ruminants is Anaplasma ovis, which parasitizes in the erythrocytes of these animals. The purpose of this study was the finding and identification of Anaplasma spp. in the blood of small ruminants using genetic methods and obtaining data on the distribution of anaplasmosis in the Irkutsk region. 20 goat blood samples, 611 sheep blood samples and 209 Dermacentor nuttalli ticks from 12 districts of the Irkutsk region were examined for the presence of Anaplasma spp. Only one type of anaplasma, A. ovis, was found among the genotyped samples. A. ovis was found in the blood of sheep and goats in all of the studied districts of the Irkutsk region. The proportion of sheep blood samples containing anaplasma DNA varied from 30 % to 85 %, in goats – from 10 % to 100 % in different districts, and averaged 57.8 % in sheep and 55,0 % in goats. Frequency of infection of D. nuttalli ticks with A. ovis was 5.7 %. The nucleotide sequences of the samples detected in the blood of small ruminants on the territory of the Irkutsk region differed from each other by a single nucleotide substitution and were identical to the sequences of the type strain Haibei, as well as the sequences of A. ovis previously found in the blood of sheep from Mongolia, deer from China, and Dermacentor niveus and Dermacentor nuttalli ticks from China. These sequences were also identical to the sequences previously found in the blood of sheep from Altai and in Dermacentor nuttalli ticks from Tuva, which indicates the wide distribution of these A. ovis genovariants in Siberia and the probable role of D. nuttalli as a carrier of the agent of anaplasmosis of small ruminants in the Irkutsk region.